Gravitational energy and radiation of a charged black hole - Combi, Luciano (2017)
We analyze the energy configuration of a charged black hole in the TeleparallelFramework of General Relativity. We obtain the energy-momentum tensor of the gravitationalfield in a stationary frame, and we calculate its contribution to the total energyof the system. We study the same gravitational field measured by an accelerated frameand we analyze how the energy-momentum tensor is transformed. We found that in theaccelerated frame, a Poyinting-like flux appears for the gravitational field but not for theelectromagnetic field.